Synchronous Pancreatic and Pulmonary Metastases from Solitary Fibrous Tumor of the Pleura: Report of a Case. (November 2017) - Tamburini, Nicola; Fabbri, Nicolò; Anania, Gabriele; Maniscalco, Pio; Quarantotto, Francesco; Rinaldi, Rosa; Cavallesco, Giorgio
Introduction: Solitary fibrous tumor of the pleura is an uncommon tumor with an indolent course and a good prognosis after surgical resection. However, the tumor occasionally follows an unpredictable clinical course and malignant transformation has been reported to increase the rate of local recurrence. Solitary extrathoracic metastasis from solitary fibrous tumor of the pleura is an uncommon finding. Case Presentation: In this case report we present the first case of a synchronous single pulmonary and pancreatic metastasis treated with minimally invasive surgery. Conclusions: Pancreatic recurrence should be considered in the postoperative follow-up in patients with solitary fibrous tumor of the pleura.